Experimental Study on the Softening Characteristics of Sandstone and Mudstone in Relation to Moisture Content - Gui-chen Li; Chong-chong Qi; Yuan-tian Sun; Xiao-lin Tang; Bao-quan Hou (Shock and Vibration)
The kinetics of fluid-solid coupling during immersion is an important topic of investigation in rock engineering. Two rock types, sandstone and mudstone, are selected in this work to study the correlation between the softening characteristics of the rocks and moisture content. This is achieved through detailed studies using scanning electron microscopy, shear tests, and evaluation of rock index properties during exposure to different moisture contents. An underground roadway excavation is simulated by dynamic finite element modeling to analyze the effect of moisture content on the stability of the roadway. The results show that moisture content has a significant effect on shear properties reduction of both sandstone and mudstone, which must thus be considered in mining or excavation processes. Specifically, it is found that the number, area, and diameter of micropores, as well as surface porosity, increase with increasing moisture content. Additionally, stress concentration is negatively correlated with moisture content, while the influenced area and vertical displacement are positively correlated with moisture content. These findings may provide useful input for the design of underground roadways.